POLA RETURN PORTOFOLIO WINNER-LOSER DI BURSA EFEK INDONESIA - Julianti, Mery (Jurnal Terapan Manajemen dan Bisnis, 2016)
The main of this research is to find patterns that form in the return stock portfolios winner and loser stocks in LQ45 Index from October 2009 to February 2016.  The pattern can be random walk, reversal and momentum. The result is expected to be a reference for investors to decision investment in the capital market.  The data analysis technique used is to divide the stage into two stages, namely stages of formation  stock portfolios winner and loser stocks and stock portfolios winner-loser testing stage.  Then from test results tested significance level by using different test techniques paired sample t-test.This research found that in the period of short-term showed results that are not consistent with the hypothesis would be found of a reversal pattern and the results were not significant.  In the mid-term test period altough that result is positive returns consistent with the hypothesis but the significant results of testing three months showed no significant results.  In the test period of 6 months and 12 months found the pattern of momentum.  And for a period of long-term testing found no reversal pattern that has been formulated previously.  Momentum patterns that actually found in the long-term period.From the results of this research can be concluded that the return pattern formed is still random walk, only the testing period of 6 months, 12 months and 36 months were found patterns of momentum.